Designing the Network of Ecological Corridors Among Organic Farms in South Bačka District of Vojvodina Province - Brankica Babec; Srđan Šeremešić; Ljiljana Nikolić; Ksenija Hiel (Fábos Conference on Landscape and Greenway Planning, 2016)
In the predominant agricultural area such as Vojvodina Province the main threat to biodiversity is the fragmentation of nature habitats. Biodiversity decline started with the large scale clearing of forest and wetlands and expansion of the agricultural. Recent biodiversity deterioration is linked with the intensive management used in conventional agriculture. Protected areas, as main source of biodiversity, covers approximately 5,5% of total of 2.150.600ha land in Vojvodina Province that is considered as insufficient for species expansion. Under the artificial cropping systems cultivated and weed species suppress native vegetation and inhibit its proliferation. Sufficient number of terms are associated with eco corridors that might lead to terms misuses. They differ in relation to the ecological significance, environmental protection, landscape and spatial planning and relationship with sustainable agriculture systems. The following terms are used for the plant belts: (i) eco corridors aims to link protected ecosystems with biological corridors and allow migration of plant and animal species, (ii) protectiveinsulation belts primarily represent the spatial isolation i.e. living belt between the surface under organic and the surfaces under conventional agriculture production. The main purpose of this belt is to prevent the influence of the application of synthetic agents that are used in the environment of organic production. (iii) Buffer zones are areas that provide and maintain the function of the protected zones and have special significance for geo-systemic balance. These are areas that are raised around potential sources of contamination i.e. all those objects that endanger the environment. This model in agriculture contributes to the protection from wind erosion. Formation of the protective-insulating belt in organic production represents a legal obligation to which the organic crop must be separated or isolated from crop under conventional production. Family farms organized according to the principles of organic production represent micro-ecosystems with its own biodiversity, and are core areas for biodiversity expansion among the agriculture areas. The main objective of this study is to access the relationship between core areas, which in this case are family organic farms, and biological corridors and to allow proliferation of plant and animal species. Based on the established link the core areas and corridors propose ecological networks with a permanent connection. The idea is to emphasize developement of ecological network which will be gradually established in the future.
Keywords: greenways; ecological corridors; south backa district; Vojvodina Province; organic farm